2010
DOI: 10.1210/en.2010-0484
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Metabolism and Human Sperm Motility: Impact of CB1 Receptor Activation

Abstract: It has been reported that the endocannabinoid anandamide (AEA) exerts an adverse effect on human sperm motility, which has been ascribed to inhibition of mitochondrial activity. This seems to be at variance with evidence suggesting a major role of glycolysis in supplying ATP for sperm motility; furthermore, the role of AEA-binding receptors in mediating mitochondrial inhibition has not yet been explored. In this study, human sperm exposure to Met-AEA (methanandamide, nonhydrolyzable analog of AEA) in the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 68 publications
0
51
0
Order By: Relevance
“…Met AEA (stable form of AEA) was shown to decrease human sperm motility and viability via its action through CB1 [69]. Several other in vitro studies on human spermatozoa are in agreement with these findings [46,47,64,107]. Whan et al [108] exposed human spermatozoa to both therapeutic and recreational levels of THC and showed clearly that it reduced the percentage of motile and progressively motile spermatozoa, while the kinematic parameters such as straight line velocity and average path velocity were also decreased.…”
Section: Effect On Sperm Parameters and Functionmentioning
confidence: 60%
“…Met AEA (stable form of AEA) was shown to decrease human sperm motility and viability via its action through CB1 [69]. Several other in vitro studies on human spermatozoa are in agreement with these findings [46,47,64,107]. Whan et al [108] exposed human spermatozoa to both therapeutic and recreational levels of THC and showed clearly that it reduced the percentage of motile and progressively motile spermatozoa, while the kinematic parameters such as straight line velocity and average path velocity were also decreased.…”
Section: Effect On Sperm Parameters and Functionmentioning
confidence: 60%
“…Human spermatozoa exhibit the complete biochemical machinery needed to synthesize (N‐acylphosphatidylthanolamine‐hydrolyzing phospholipase D, NAPE‐PLD) and degrade (fatty acid amide hydrolase, FAAH) AEA (Francavilla et al ., ), to synthesize (phospholipase C and diacylglycerol lipase) and degrade (monoacylglycerol lipase) 2‐AG (Lewis et al ., ) and express receptors for (endo)cannabinoids: CB1 (Rossato et al ., ; Francavilla et al ., ), a non‐functional CB2 (Francavilla et al ., ; Agirregoitia et al ., ) and the transient receptor potential vanilloid 1 (TRPV1) receptor (Francavilla et al ., ). We have previously demonstrated that the CB1 activation by methanandamide (Met‐AEA), non‐hydrolyzable analogue of AEA, inhibited sperm mitochondrial membrane potential (ΔΨm) (Barbonetti et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Evidence has been produced that both in mouse [14] and human spermatozoa [15,16] glycolysis compensates for any lack of ATP production by mitochondria in maintaining sperm motility. However, independently from the impaired mitochondrial ATP generation, a mitochondrial dysfunction could affect sperm motility, when it is accompanied by increased intrinsic mitochondrial generation of ROS.…”
Section: Introductionmentioning
confidence: 99%